The Effect of Profitability and Liquidity on Tax Aggressiveness with Corporate Social Responsibility Disclosure as a Moderating Variable : The Effect of Profitability and Liquidity on Tax Aggressiveness with Corporate Social Responsibility Disclosure as a Moderating Variable - Amelia Lensi Matei; I Dewa Nyoman Badera (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Tax aggressiveness refers to corporate actions aimed at reducing taxable income through tax planning strategies. This study aims to provide empirical evidence regarding the effect of profitability and liquidity on tax aggressiveness, with corporate social responsibility (CSR) disclosure as a moderating variable. This research is based on agency theory and focuses on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The study sample consists of 87 companies, selected using a purposive sampling technique. The research employs Moderated Regression Analysis (MRA) to analyze the data. The findings indicate that profitability significantly influences tax aggressiveness, while liquidity does not. Additionally, CSR does not moderate the relationship between profitability and tax aggressiveness, nor does it moderate the effect of liquidity on tax aggressiveness. The theoretical implication of this research supports and expands the understanding of agency theory in tax-related decision-making. The practical implication suggests that highly profitable companies should avoid engaging in tax aggressiveness, as it may damage their corporate image. Moreover, fair tax policy implementation and enhanced government supervision are necessary to minimize tax avoidance practices